Skorost' bega i sposobnost' k vosproizvedeniyu ritma v cravnenii s rezul'tatami v bege s bar'erami y 13-15-letnikh netreniruyushchikhsya devochek i mal'chikov - Iskra, Ya. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of the investigation was to determine the relationships; (a) between the 60 m hurdles and 60m; (b) between the 60 m hurdles and three rhythm tests (Mynarski's test, rhythm reconstruction while marching, rhythm reconstruction fostered by a stop-watch). Forty-four boys and forty girls aged 13-15 years participated as subjects in the continuous investigation carried out from 1996 to 1998. Analysis of correlation coefficients between the 60 m hurdles and selected tests showed that this event is mainly of speed character (r = 0,66 - 0,86; p<0,01). As for a the rhythm reconstruction tests are concerned, the most useful diagnostically are the Mynarski's test in girls and the test with a stop-watch in boys.